PENGARUH KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA DENGAN MEDIASI KEPUASAN KERJA PERAWAT DI RUANG RAWAT INAP RSUD KARDINAH KOTA TEGAL - Nur Fitriani; Mr. Basukiyatno (Program Studi Magister Manajemen, Universitas Pancasakti Tegal - Indonesia, 2018)
The purpose of this study is to examine and analyze the effect of compensation and organizational culture on performance by mediating job satisfaction of nurses. In this study, the population was all nurses in the Civil Hospital inpatient Kardinah. The sampling method using purposive sampling. Retrieval of data using questionnaires. Tests conducted by the research instrument validity and reliability, statistical test equipment being used is multiple regression analysis, R2 test and t-test, to test the significance of regression coefficients generated. The results showed that compensation is positive and significant effect on affective commitment, job satisfaction and commitment continuants, but had no effect on performance. Organizational culture of innovation and risk-taking has positive influence on affective commitment and performance. Results-oriented organizational culture has a positive effect on job satisfaction and performance. People-oriented organizational culture has a positive effect on job satisfaction. Affective commitment and commitment continuants positive effect on job satisfaction but had no effect on performance. Job satisfaction has a positive effect on performance. Affective commitment, job satisfaction and commitment continuants is purely capable of mediating variables to explain the effect of indirect compensation to performance. Affective commitment and job satisfaction are not able to explain the indirect effect of organizational culture of innovation and risk-taking on the performance of nurses in hospitals Kardinah Tegal City.Keywords: compensation, organizational culture, , job satisfaction and performance of nurses